2017
DOI: 10.3748/wjg.v23.i23.4191
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chronic cholestasis without liver cirrhosis - Creation of an animal model

Abstract: AIMTo analyze time intervals of inflammation and regeneration in a cholestatic rat liver model.METHODSIn 36 Lewis rats, divided into six groups of 6 animals (postoperative observation periods: 1, 2, 3, 4, 6, 8 wk), the main bile duct was ligated with two ligatures and observed for the periods mentioned above. For laboratory evaluation, cholestasis parameters (bilirubin, γ-GT), liver cell parameters (ASAT, ALAT) and liver synthesis parameters (quick, albumin) were determined. For histological analysis, HE, EvG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Similarly, some studies demonstrated reduced bone formation and increased bone resorption in BDL male rats, 27,28 which is in accordance with the PBC patients 30 . The BDL male rat model used in the present study was simple and effective, as described previously 27,28,31 . Many scholars considered that cholestasis is one of the major risk factors of impaired bone formation 32 .…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, some studies demonstrated reduced bone formation and increased bone resorption in BDL male rats, 27,28 which is in accordance with the PBC patients 30 . The BDL male rat model used in the present study was simple and effective, as described previously 27,28,31 . Many scholars considered that cholestasis is one of the major risk factors of impaired bone formation 32 .…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have demonstrated that down-regulation of Cdkn1a , also known as p21 , stimulates liver regeneration, while overexpression inhibits this process [36,37,38]. Furthermore, a recent report of Cdkn1a up-regulation resulting from acute cholestatic injury was proposed as a biomarker for impaired liver regeneration [39]. Elevated total bilirubin in conjunction with up-regulation of Cdkn1a and a number of other gene-markers of cholestatic liver injury (i.e., Abcb1a , Abcc2 , Abcc3 , Atp8b1 , and Rdx ) and down-regulation of fatty acid metabolism-related genes ( Car3 , Fabp1 , and Ppara ) observed in our study, suggest that CBD-induced liver injury may be cholestatic, though ALP and GGT were not elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is highly possible that quercetin may be effective in prohibiting oxidative stress induced liver injury in chronic cholestasis. Thus, the present study was planned to investigate the possible protective effect and the related mechanisms of quercetin against cholestasis induced by bile duct ligation in rats, a well settled experimental model of cholestasis that initiates a complex cascade of pathological events similar to that of human [12].…”
Section: Introductionmentioning
confidence: 99%